Knowledge, Attitudes and Perception toward COVID-19 Vaccines among Adults in Jazan Province, Saudi Arabia - Edrous Alamer (MDPI AG, 2021)
Background: Saudi Arabia is one of the countries that initiated early vaccination programs despite the global challenges concerning the availability of COVID-19 vaccines. Massive vaccination campaigns have been undertaken in the country; however, negative perception and hesitancy toward vaccines may exist which could reduce public response to vaccination. Further, studies evaluating the current perception and attitude toward COVID-19 vaccines are scarce. Thus, this study aims to assess the community attitudes and perceptions toward COVID-19 vaccines in Jazan Province, Saudi Arabia. Methods: A cross-sectional, retrospective study using an online questionnaire was conducted among the public in Jazan, the southern region of Saudi Arabia. General and demographic data were collected, and perception and attitude toward COVID-19 vaccines were evaluated. Results: Most participants in this study were female (67%) with a median age of 23 years. The majority held a bachelor’s degree, and they trusted the Saudi healthcare system. Our survey showed that 67% of the study participants had positive perceptions toward COVID-19 vaccines, a finding that is significantly associated with receiving the influenza vaccine in the past, the existence of trust on the current healthcare system and holding positive beliefs toward the effectiveness of the current COVID-19 vaccines in reducing the risk of infection, complication, and mortality. Conclusions: The proportion of the public in Jazan who believed in the COVID-19 vaccine effectiveness is not inferior from similar international reports. Thus, national awareness programs toward the effectiveness of the vaccine could be enhanced to accelerate vaccination coverage. Further, nationwide surveys are warranted to include larger populations from different communities to assess the overall perception toward COVID-19 vaccines in the whole country.